Genetic constraints of population expansion of the Carpathian lynx at the western edge of its native distribution range in Central Europe - Krojerová-Prokešová, J; Turbaková, B; Jelenčič, M; Bojda, M; Kutal, M; Skrbinšek, T; Koubek, P; Bryja, J (Heredity, 2019)
Even though populations of many large carnivores are expanding throughout Europe, the Eurasian lynx population in the Western Carpathians seems unable to spread beyond the western boundaries of its current distributional range. Many factors, both extrinsic and intrinsic, can influence the potential for range expansion: landscape fragmentation, natal philopatry, low natural fecundity and high mortality, and low and sex-biased dispersal rates. In this study we used non-invasive genetic sampling to determine population size fluctuation, sub-structuring and social organisation of the peripheral lynx population at the Czech-Slovak border. Even though the population size has been relatively stable over the period studied (2010-2016), the individual inbreeding coefficients of residents at the end of the study were much higher than those of founders at the beginning of the study. While non-resident individuals (predominantly males) occurred regularly in the study population, only resident individuals with well-established home ranges participated in breeding and produced offspring. Almost half the offspring detected in the study (predominantly females) settled in or near the natal area. Subsequent incestuous mating resulted in production of inbred individuals, reduction of effective population size of the population, and sub-structuring of the population through formation of two distinct family lineages. Our study illustrates how social constraints, such as territoriality, breeding of residents and natal philopatry of females, lead to incestuous mating in small-sized populations, especially at the periphery of their distribution. This threat should be taken into account in planning of conservation and population recovery of species with similar social structure.
Keywords: Breeding; populační genetika; Genetics, Population; Carnivory; Female; chov; Lynx; rozšíření zvířat; inbreeding; zvířata; Animal Distribution; Europe; masožravci; ženské pohlaví; Male; Inbreeding; Animals; mužské pohlaví; Evropa